Etiology, 3-Month Functional Outcome and Recurrent Events in Non-Traumatic Intracerebral Hemorrhage - Goeldlin, Martina B.; Mueller, Achim; Siepen, Bernhard M.; Mueller, Madlaine; Strambo, Davide; Michel, Patrik; Schaerer, Michael; Cereda, Carlo W.; Bianco, Giovanni; Lindheimer, Florian; Berger, Christian; Medlin, Friedrich; et al. (Journal of Stroke, 2022)
Background and Purpose Knowledge about different etiologies of non-traumatic intracerebral hemorrhage (ICH) and their outcomes is scarce. Methods We assessed prevalence of pre-specified ICH etiologies and their association with outcomes in consecutive ICH patients enrolled in the prospective Swiss Stroke Registry (2014 to 2019). Results We included 2,650 patients (mean??standard deviation age 72??14 years, 46.5% female, median National Institutes of Health Stroke Scale 8 [interquartile range, 3 to 15]). Etiology was as follows: hypertension, 1,238 (46.7%); unknown, 566 (21.4%); antithrombotic therapy, 227 (8.6%); cerebral amyloid angiopathy (CAA), 217 (8.2%); macrovascular cause, 128 (4.8%); other determined etiology, 274 patients (10.3%). At 3 months, 880 patients (33.2%) were functionally independent and 664 had died (25.1%). ICH due to hypertension had a higher odds of functional independence (adjusted odds ratio [aOR], 1.33; 95% confidence interval [CI], 1.00 to 1.77; P=0.05) and lower mortality (aOR, 0.64; 95% CI, 0.47 to 0.86; P=0.003). ICH due to antithrombotic therapy had higher mortality (aOR, 1.62; 95% CI, 1.01 to 2.61; P=0.045). Within 3 months, 4.2% of patients had cerebrovascular events. The rate of ischemic stroke was higher than that of recurrent ICH in all etiologies but CAA and unknown etiology. CAA had high odds of recurrent ICH (aOR, 3.38; 95% CI, 1.48 to 7.69; P=0.004) while the odds was lower in ICH due to hypertension (aOR, 0.42; 95% CI, 0.19 to 0.93; P=0.031). Conclusions Although hypertension is the leading etiology of ICH, other etiologies are frequent. One-third of ICH patients are functionally independent at 3 months. Except for patients with presumed CAA, the risk of ischemic stroke within 3 months of ICH was higher than the risk of recurrent hemorrhage.
CRIS-Team WoS Importer:2022-07-08